Secretome Analysis of Macrophomina phaseolina Identifies an Array of Putative Virulence Factors Responsible for Charcoal Rot Disease in Plants - Sinha, Nilanjan; Patra, Sourav Kumar; Ghosh, Sanjay (Frontiers in Microbiology, 2022)
Macrophomina phaseolina is a global devastating necrotrophic fungal pathogen. It causes charcoal rot disease in more than 500 host plants including major food crops, pulse crops, fibre crops and oil crops. In spite of having the whole genome sequence of M. phaseolina, understanding of the M. phaseolina genome-based plant-pathogen interactions is limited in the absence of direct experimental proof of secretion. Thus it is essential to understand the host- microbe interaction and the diseases pathogenesis which can ensure global agricultural crop production and security. An in-silico predicted secretome of M. phaseolina is unable to represent the actual secretome. We could identify 117 proteins present in the secretome of M. phaseolina using LC-ESI-MS-MS. An array of putative virulence factors of M. phaseolina were identified in the present study using solid state culture. Similar virulence factors have been reported in other plant pathogenic fungi also. Among the secretory fungal proteins with positive economic impacts, lignocellulolytic enzymes are of prime importance. Further, we validated our results by detecting the cell wall degrading enzymes xylanase, endoglucanase and amylase in the secretome of M. phaseolina. The present study may provide a better understanding about the necrotrophic fungi M. phaseolina which modulate the host plant defense barriers using secretory proteins.